Recent advances in engineered polymeric materials for efficient photodynamic inactivation of bacterial pathogens - Sathishkumar Gnanasekar; Gopinath Kasi; Xiaodong He; Kai Zhang; Liqun Xu; En-Tang Kang (Bioactive Materials, 2023)
Nowadays, infectious diseases persist as a global crisis by causing significant destruction to public health and the economic stability of countries worldwide. Especially bacterial infections remain a most severe concern due to the prevalence and emergence of multi-drug resistance (MDR) and limitations with existing therapeutic options. Antibacterial photodynamic therapy (APDT) is a potential therapeutic modality that involves the systematic administration of photosensitizers (PSs), light, and molecular oxygen (O2) for coping with bacterial infections. Although the existing porphyrin and non-porphyrin PSs were effective in APDT, the poor solubility, limited efficacy against Gram-negative bacteria, and non-specific distribution hinder their clinical applications. Accordingly, to promote the efficiency of conventional PSs, various polymer-driven modification and functionalization strategies have been adopted to engineer multifunctional hybrid phototherapeutics. This review assesses recent advancements and state-of-the-art research in polymer-PSs hybrid materials developed for APDT applications. Further, the key research findings of the following aspects are considered in-depth with constructive discussions: i) PSs-integrated/functionalized polymeric composites through various molecular interactions; ii) PSs-deposited coatings on different substrates and devices to eliminate healthcare-associated infections; and iii) PSs-embedded films, scaffolds, and hydrogels for regenerative medicine applications.